Spectroscopy and electrochemical characterization of Langmuir-Blodgett and physical vapor thin films of 29-membered diazocrown ether 1 with two n-octyl substituents - Shimizu, Flavio M. [UNESP]; Ferreira, Marystela; Skwierawska, Anna S.; Biernat, Jan F.; Giacometti, Jose A. [UNESP] (Elsevier B.V. Sa, 2012)
UV-vis and FTIR spectroscopy and electrochemistry studies were performed on Langmuir-Blodgett (LB) and on physical vapor deposition (PVD) films of 29-membered diazocrown ether with two n-octyl substituents. FTIR and UV-vis measurements showed that PVD and LB films have distinct bands and dissimilarities in their intensities. PVD and LB films on ITO electrodes were also used as electrodes in cyclic voltammetry. Voltammograms showed that PVD and LB films have a distinct response for ions K+, but only LB film has specific selectivity to K+ ions. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Azocrown ether; Cyclic voltammetry; Langmuir-Blodgett film; PVD film; UV-vis spectroscopy; FTIR spectroscopy